SEPTEMBER 2014 PLACEMENT ADS (The Accounting Review, 2014)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for up-to-date, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.HUNAN UNIVERSITY, Business School is seeking candidates in accounting at all different levels (Assistant, Associate, and Full Professors) starting the 2015–2016 academic year. All ranks will be considered. Applicants must have a doctorate degree in accounting or related fields (finance, economics, etc.) by August 2015. If you have had papers published, then we can promise a higher level of salary. Hunan University is a comprehensive and research-oriented university in China, under the Ministry of Education, “Project 211” and “Project 985.” The Business School of Hunan University prides itself on the 100-year history of business education, which dates back to the establishment of Hunan Business Educator Training Institute in 1911. Accounting is now in a rapid growth rate and we in great need of teachers with good research levels and teaching ability. We offer competitive compensation packages that include salary, relocation, research funds, and housing subsidies. To apply, please submit a letter of application, curriculum vita, sample research papers, and three reference letters electronically to: Professor ZhiYang at yangmkt@126.com and Professor Fangfei Ding at dff@hnu.edu.cn.ROBERT MORRIS UNIVERSITY (RMU), founded in 1921, is one of the leading universities in the Pittsburgh region. RMU provides a professionally focused education with an emphasis on engaged learning and is one of the most affordable private master's-level institutions in Pennsylvania. For 2014–2015, RMU seeks faculty candidates who will exemplify the or should have a in the of with a for in accounting information should have an doctorate or an in Business an Applicants must in teaching and research in to: should submit a letter of and of three academic or by to: University For information we that our to a is and and and UNIVERSITY seeks candidates to and accounting research leading to and provide to the and positions are must or by August a in Business with a in or related degree an must be under and at the in teaching and and an research must be to two or at the and in at one teaching For please submit one letter of and application, vita, of all and universities sample of of teaching and of to: of of Business University or University is an UNIVERSITY, of Accounting for or Professor positions in The of Accounting is and provides a emphasis on and are to the for in teaching and include a or in degree an is with degree will be considered. and in accounting are The will have a teaching in or The teaching is is with and The will August 2015. To please an application with a letter of application and to posting by August The University is an candidates are to UNIVERSITY, School of Business and for a faculty position at the or Professor level in the of Accounting starting August 2015. interested in or Accounting are all of are to The will be to or a research and in teaching in the and accounting degree must have a in should a letter of application for the a three a research and a teaching The position will For should be by Applicants should with a letter that a teaching and research University is an which for and with UNIVERSITY, of of and is for a position in Accounting at the Professor with a The and that have The included by the Review in of Business in the The a in Accounting of the in Accounting an in Accounting for an accounting of the on the have by our The in is one of the and in the The more in should have a in an Accounting an with of or for teaching and The will be to and accounting and are competitive with or and relevant are For information contact the Professor at Accounting for Professor positions in the of and Accounting 2015. Applicants should have a degree in with in related fields and will be considered. The of Business and is must be under will be to with and accounting The Accounting to be the comprehensive university accounting by on a research and The position is For more information about our go to: To apply, a letter of application, contact information for three and of teaching will be of should be to: at or to: and Accounting University of will be considered. by are will is an UNIVERSITY School of Business and is by We a or Professor of Accounting for academic year. position a teaching of three in the of and accounting at the include research and publication is doctorate or in Accounting an is August will be on an and the will the position is To a vita, three letters of and teaching to: School of Business and University University is to The University and of of with and of School of Accounting one or more faculty positions at the or in 2015. Applicants to at the and levels with an in will be considered. to in teaching and and the to research are are is a in and one of the The business a by the and the The is in and is an of and is a information about the can be on the application at our and letters of teaching and of All must be For please contact the at Review will and will an is for will be in 2015. Position is The is an The of on for UNIVERSITY for a position in the of which is available August 2015. doctorate with emphasis in Accounting and a to Business accounting be of prior to is or more of the and is The position will submit a letter of application, vita, and three letters of reference to: Accounting of to is information about this position is available by or by is an UNIVERSITY, School of Accounting for starting August or The will be on a with the of or on for candidates. We offer competitive salary, research funds, and housing candidates please submit a and research three reference letters should be to: School of Review of will UNIVERSITY, of Business of Accounting is seeking candidates for a Professor position 2015. University and is in of with to and The is and accounting The of Accounting information the of Business and the of Accounting can be or at must have a or in Accounting an be under be to and for research and is candidates contact University is a of The University and is an School of Business is seeking two faculty at the of Professor of August 2015. doctorate in Accounting or an an is will be to candidates who are research and to or are To apply, please the application and a letter of and a three letters and a to: Accounting University of Review of The University the to the or to the The must be to in the is an UNIVERSITY for a or Professor position in Accounting to August 2015. The provides a emphasis on and include a or in degree an is to will be considered. and in accounting are teaching include accounting The teaching is an application with a letter of application and to posting by August position is The University is an candidates are to UNIVERSITY for an faculty position in on If the is August 2015. The must have in and The teaching is at and levels and The is for will be to candidates who a an university and who have in accounting or Applicants must be on will be the position is application vita, teaching and three letters of reference to: Accounting and of is an to the of and for UNIVERSITY, is an or Professor in position is a We or in accounting to for this in teaching and of learning in an education to and to and with accounting and to with in teaching and submit and letter on UNIVERSITY, of for two faculty positions at the or starting 2015. position is in and the is in about positions can be at the in Business with an accounting emphasis an university our for For the position we will candidates with or is for include a to teaching at the and leading to and and university and is competitive the and with and Applicants should a letter that in and for the a curriculum that history dates of and contact information of three of teaching and a should be to: Professor at Review of will and a is University is to The University and of of and of will be to a UNIVERSITY for two or Professor positions in or or accounting be considered. degree in accounting or or must degree by of the year. will of or include teaching University and is on the and the is must include application letter how are curriculum of teaching and of three All application must be the for positions are UNIVERSITY, School of with of and with an Accounting is seeking Accounting candidates with a in to a Professor position in 2015. in Accounting or a related with a on or a related an is will be considered. and a in an will be considered. teaching or in accounting is a in a is a will be to candidates who faculty for a job and information about and submit a letter of application the position a curriculum and the and of at three to: and to UNIVERSITY, School of Business for a position in accounting to 2015. is to at the or Professor ranks will be considered. provides a for research a teaching for a and and Applicants for the position must a in accounting by the of the in teaching and should submit to the website University is a research a research of of The School of Business is by the to of and are by the The University is in to the the We are of the of the with our at and For contact University a faculty and and candidates. The University is an for a Professor in accounting 2015. should have a in accounting or have a in accounting and with teaching The will teaching a to education in a and the to with to education of the must be to accounting at the and in teaching in and is should be to: and should include a on research and on teaching and teaching should to have three letters of will to be the position is is to the of and of who will that is an UNIVERSITY, of and Business for a position at the Professor level to in August 2015. should a or in accounting at the of and be to and accounting The of Business is and about The and a of University is in which is an The a of and about For more the to teaching and a to academic research will be and accounting will be a and are Review of will To apply, submit a letter of application, a curriculum vita, and contact information for three to: should be to: at or at will be the position is UNIVERSITY of Accounting and for an Professor of is a accounting position to in and provide or in accounting an is a letter of how you the for the curriculum of teaching of and and a of three and will be and the position is is 2015. is a which a The University of at is an UNIVERSITY, School of of Accounting for an to August 2015. The position is of by the of The School of Business at University is the business in the the of Accounting and the School of Business are by the of our accounting are by Applicants with a in will be at the Professor The position that the degree in Accounting be or by the of August 2015. is The Professor is to and be in academic and provide to the and the of or in teaching and research is University is a and of to be about and to a to that University seeks to and a and candidates can contact at UNIVERSITY, a to and is seeking for a position in Accounting at the Professor 2015. be considered. must a to teaching and research and to the and University is in to teaching and is and all will be candidates with a teaching in are to in Accounting is candidates be under is candidates must and submit a letter and curriculum All this position can be to: of School of University is an and of and application and UNIVERSITY, of Business and of Accounting seeks research with and for two positions at the Professor to Accounting faculty in 2015. must be to one or more of the Accounting and at the and levels and academic accounting should and and be to in a with a and must accounting teaching and research of the accounting and the of the the and the accounting a accounting a in Accounting and the business to are to If please a letter of curriculum letters of and or electronically in of Professor Professor of Accounting and of University provides comprehensive and candidates are to University is an UNIVERSITY, of Business and is seeking and for the position of Full Professor and and to Accounting faculty in 2015. for the position must have a in accounting with a of research and in teaching are in the Accounting and Accounting at and we will candidates in Applicants should and to in the of the and the and must teaching and research and the of the the and the The of Business and at University is to the and of the and accounting accounting in Accounting and business to of and the are to to this For information Professor of Accounting and of of Business and University provides comprehensive and candidates are to University is an UNIVERSITY is seeking candidates. candidates will have a or with an accounting a by the and be of all for the degree are All accounting will be considered. will for in and in teaching at an prior accounting and in in teaching accounting information The a in Accounting and an in Accounting and and in the and is competitive with To apply, please and will be to submit a curriculum vita, of the degree and three reference UNIVERSITY, of Accounting for a position at the or level in 2015. is a university in the School of and Applicants should have a doctorate or be to and have teaching in to are to research in To the School to available should electronically submit a curriculum of teaching and and three letters of reference to: will be or about the position should be to: who is this University is an UNIVERSITY, School of of for a position available August 2015. We candidates with a degree in or an or by be considered. must be to in and and University and candidates will have a teaching in academic and research are application For or to a of is an and a to the of UNIVERSITY School of Business for two Professor of Accounting positions in starting 2015. in Accounting or related doctorate by August will be considered. are to two then Position to in is Position to in accounting information is a accounting will be considered. For a of is a For is to teaching and publication is and prior is For please our website Review of will and the position is in Accounting or related doctorate by August will be considered. To Applicants should submit a curriculum and contact information for to: to the etc.) should be to: Professor of School of Business For more about at and to the which information about and and please go to: which will provide you with on how to a of the is an and is to to and UNIVERSITY, School of and seeks to a position in Accounting of all ranks will be considered. should a doctorate or be to of the doctorate in accounting or accounting information The be to accounting or accounting information in teaching is UNIVERSITY, School of and seeks to a position in of all ranks will be considered. should a doctorate or be to of the doctorate in The be to Accounting or in teaching is all to: at UNIVERSITY, of Accounting for two August 2015. Applicants must have a in Accounting to degree prior to the and a to will be to candidates a or for a or for teaching in the an research and a in Accounting an a a vita, of research papers, of teaching and contact information of three should be to: will and will the positions are The position is available at is an and on all UNIVERSITY The School of for an Professor position in the of and accounting for 2015. research and a teaching in and accounting are Applicants should have a or in accounting or business by August 2015. research teaching and business and are positions are For information of will and is on an 2015. If provide vita, three and of teaching and to: Professor The School of is an UNIVERSITY The School of for an Professor position in for 2015. research and a teaching in are Applicants should have a or in accounting or business by August 2015. research teaching and business and are positions are For information of will and is on an 2015. If provide vita, three and of teaching and to: Professor The School of is an School of Accounting and is seeking to at one faculty position at the or level to August 2015. All research will be considered. Applicants are to have a in Accounting or a relevant to in academic and have a or teaching at the and For must be with a curriculum or job and of teaching ability. The Position is The application deadline is is for The University of to a of and will or of or or UNIVERSITY, School of Business for and faculty positions in candidates at all levels and of who are interested in and should have or to a by and should a and research The will be to research and to and in should include and of research Applicants are to submit electronically by and curriculum research papers and and teaching on that all be by to: or by to: of School of and can for For an application to be all must have three letters of to the or The application deadline is University is an and is to the of of and of and with who to the and UNIVERSITY of Business and of Accounting in for a position at the Professor level in in the of The University of is a comprehensive university with in the of a with the of a is at the of and the two in the and is to and and accounting have and in The of Business an of and The Accounting a with Accounting and a of in The is with the of in the or in Business an with a in Accounting is by is for at the Professor Applicants should for research and with teaching in are or will be a to Applicants must in to be for the Review of will this and will the position is application must a curriculum of research and a of three with contact and job teaching submit all the University of application The University of is an and and on the of or UNIVERSITY, interested in our and faculty 2015. is by The to of Business The of Business a faculty positions in For please is an and who are to in the School of Accounting and for a or position in the of August 2015. are for and at a teaching are academic for research are to have a teaching for the three position is at the Associate, or Full should be focused on publication in the most for a position should have a of in teaching and research to an of an research and the and to with for a position should have of research and teaching in accounting must be by the and are competitive and with and are The Accounting at the and is by the For information about the School and faculty and For of or to application School of University of will a letter of and a of and the and contact information for at three To please faculty with or will and will the position is The University of on the of a and information in the and The to the of the of and of is faculty for at all at ranks must a and candidates for Professor positions must or be of a Applicants for positions should have a research and the to in education and curriculum at the and and positions are Applicants should submit a that research and is competitive and will be with the level and For please and curriculum teaching research papers, and the and or of three will be the should be by 2015. and should be by 2015. and be the all by the will for an letter please which you are For information application you for is an and all will for to a or a with a with and who and and UNIVERSITY, of Business is seeking to our For information about the position and how to apply, please go to: or an to: deadline is or is an of with and and that to to a faculty and and to to a All are and and will UNIVERSITY of Business for a or Full Professor in to in research and teaching at the and levels is in all accounting are to and are competitive with research The starting is August 2015. All will be The of will and will be the position is degree an in the of accounting or related is must have an research with the level of candidates should contact The University of at is an of and with are to Applicants are to a UNIVERSITY of of Accounting for a August 2015. include a a of teaching in accounting for a and a to and are a in Business in Accounting and a We offer a competitive compensation To apply, go to: and reference will be to a of teaching of with and and provide the for at three letters of position you are The University of is an All are to and will for free on the of a with a or a will be for in the UNIVERSITY candidates for a position or Professor to and 2015. with in accounting are in or will be considered. or and to accounting at the and levels is candidates of is and in the accounting is and a to in the business and is teaching is three with teaching at our leading to publication in UNIVERSITY, School of is seeking an who an or in accounting or related with a in at of of August 2015. are to all for the the of If all for the have a at the of at a salary, will be is should be to research and Professor are to and must have a publication in and of teaching For more letter of application, contact information for three and to: School of University Review of will August and the position is is an of with and and that to to a faculty and and to to a All are and and will UNIVERSITY, for or Professor position in accounting to 2015. The are to or academic research in and provide to the should have an in Accounting an the of is in with the of Business and have a of teaching and and have or and in the accounting are Review of will August and will the position is a letter of a and of and three letters of to: of Accounting and or the job posting and UNIVERSITY and for the of the of one of the and business in the the of Business research is and and faculty and faculty in the of and of in the of the University is on the of the that have a for an The deadline is The is is an and on all UNIVERSITY for a at the or Professor and research in with a emphasis in with the of the School of The School of a emphasis on and teaching and business are of all faculty The School of Business in business and The a or degree in accounting an be considered. The Professor a research and of is a two and are of Accounting is seeking an Professor to a of faculty or who are to and accounting by the of Business the in Accounting and comprehensive level is a university with a The of is a with housing and and or in Accounting an will be of all degree is one of Applicants with in the of are will be must be the application position is to a and history or history information an in the of a to the of the information will be in a with and UNIVERSITY, School of Business and of seeks a faculty in Accounting August position of the School are at in and at in and The must have an doctorate in Accounting or be in the of or is The at the and level will be salary, and are with is with the of is the of to the and academic a that and the and of the To apply, please by the a curriculum and that and to the all to: of We will on an starting with by August University is an and on the of or by or UNIVERSITY, School of and seeks for two positions at the are to a or in accounting an or be with degree by 2015. with teaching and research in or accounting are and and with the accounting include teaching will positions are is The University is of and of and an of or letters of electronically to: and to of the University of UNIVERSITY, of Accounting for positions at the or 2015. must have a doctorate in Accounting by August 2015. All candidates should a to research and in with teaching and in are to apply, with a for in accounting and is Professor of or To for this please an with an letter of and curriculum be to submit three letters of and to the of the a comprehensive university in the of higher education, seeks professionally who and to academic the education of the and the of a is an to an learning and are to for more UNIVERSITY, of of Business for a position an Professor in the of The position August with that include and teaching accounting will be to candidates who have a teaching in accounting and an in an of doctorate in accounting an is will be the degree is by of must have a of or the to in academic accounting and have a to with The must be letter of application and curriculum to an to an of that will be to the faculty and and three letters of The application must be to be considered. must submit will August and will the position is are to be to Professor is an Educator and of or of or are to for who under the with are available and All must by the and School of Business and of Accounting a Professor position available 2015. and include and Applicants must have a degree with by a in or Business with a in an or more of the for the degree can be If the is for more two then must be at to a of for is is the to a research in teaching or and for a faculty position are For a position and information on how to for will be The University of is an Educator and for an Professor position for August 2015. will be to with teaching in of or must have the with an accounting and are for is is and The the accounting degree and two in Accounting and in with about The accounting at the and should a to: Professor of of Business University of The University of is an and with are to a leading and in and is interested in and for in and provides an and our by our in and an compensation the more to a we a that is and Career to the academic with faculty in a that the of the academic and business We candidates who have in accounting with the to academic research to and of We are interested in candidates with an in or and We candidates for more sample research and three letters of reference our UNIVERSITY, of is seeking to one position at the Professor We are interested in with one of the or a on with a or in will be for the with a in will is a and university in The and business are by We with who can be and good The degree is a or with a in accounting an and in or and are should contact at for is an